Effect of Acetyl Salicylic Acid (ASA) in Drinking Water on Productive Performance and Blood Characteristic of Layer Hens During Heat Stress - Mohammed, Abdullah A. (International Journal of Poultry Science, 2010)
Effect of Acetyl Salicylic Acid (ASA) on hen day egg production, egg quality and blood characteristic during periods of heat stress was studied in layer hens. Four treatments with three replicated of six hens each were given 0, 0.5, 1.0 and 1.5 g/L ASA in drinking water from 58-68 weeks of age. Hen day egg production, egg weight, shell thickness and shell percentage were significantly (p<0.05) increased for hens watered 0.5, 1.0 and 1.5 g/L ASA. RBC, Hb, WBC and PCV did not show significant differences, but glucose, cholesterol and H/L of treated hens significant (p<0.05) low. There is new evidence that layer hens can make their own salicylic acid but adding 0.5, 1.0 or 1.5 g/L ASA significantly (p<0.05) increased SA in serum 18.70, 25.12 and 31.29 μg/ml respectively.